Effect Of Lead-free Solder And Gold Content On The Shear Strength, Toughness, IMC And Void Formation [TT267. C518 2004 f rb Kejuruteraan] [Microfiche 7715]. - Oo, Cheng Ee (2004)
Study of interaction between lead free solder with gold and the mechanical toughness,shear strength of solder that associated with intermetallic compound IMC and void formation was carried out.